Optical near-field measurement for spin-orbit interaction of light. (August 2021) - Shi, Peng; Yang, Aiping; Meng, Fanfei; Chen, Jiashuo; Zhang, Yuquan; Xie, Zhenwei; Du, Luping; Yuan, Xiaocong
Abstract: Since the seminal work by J. H. Poynting, light has been known to carry momentum and angular momentum. The typical dynamical features of light and its interactions—termed spin–orbit interactions (SOIs), which have been investigated intensely over the last 30 years—play a crucial role in various light-matter interactions, for example: spin Hall effect, spin–orbit conversion, helicity-controlled unidirectional excitation of light, and their inverse effects, which leads to plenty of applications including optical manipulation, communications, imaging, sensing, nanometrology, on-chip optoelectronic technologies and interdisciplinary researches. In particular, the SOI of light in isotropic inhomogeneous media is a fine, subwavelength effect accomplished through the intrinsic coupling between light's phase, polarization and position. Therefore, the traditional methods of near-field measurements, such as near field scanning optical microscopy (NSOM), have been widely employed to reveal the optical SOIs intuitively by measuring the intensity of light. Very recently, with modern advanced nanofabrication techniques, many measurement techniques based on nanoparticles, nanoantennas, and nanoprobes of special designs have been proposed to understand the optical SOIs visually by characterizing the polarization and spin/orbital features of light. This endeavor has led to the development of chiral quantum optics, spin optics, and topological photonics, and resulted in novel applications requiring optical manipulations and angular momentum communications, chiral imaging, nanometrology, and robust spin-based devices and techniques for quantum technologies. Here, we review the near-field techniques for measurements of optical SOIs together with their potential applications. We start with a theoretical overview of momentum and angular momentum properties of generic optical fields and typical phenomena involving optical SOIs. Then, we overview the theoretical basis and latest achievements of the near-field measurement techniques, including NSOM, optical manipulations, nanoantenna, and nanoprobes of special designs, all relevant to optical SOIs. A comprehensive classification is then constructed of all known methods of optical near-field measurements for the SOI of light and novel techniques identified for future applications.